Developing a mathematical model of intracellular Calcium dynamics for evaluating combined anticancer effects of afatinib and RP4010 in esophageal cancer - Chang, Yan; Funk, Marah; Roy, Souvik; Stephenson, Elizabeth R; Choi, Sangyong; Kojouharov, Hristo V.; Chen, Benito; Pan, Zui (International Journal of Molecular Sciences)
Targeting dysregulated Ca2+ signaling in cancer cells is an emerging chemotherapy approach. We previously reported that store-operated Ca2+ entry (SOCE) blockers, such as RP4010, are promising antitumor drugs for esophageal cancer. As a tyrosine kinase inhibitor (TKI), afatinib received FDA approval to be used in targeted therapy for patients with EGFR mutation-positive cancers. While preclinical studies and clinical trials have shown that afatinib has benefits for esophageal cancer patients, it is not known whether a combination of afatinib and RP4010 could achieve better anticancer effects. Since TKI can alter intracellular Ca2+ dynamics through EGFR/phospholipase C-γ pathway, in this study, we evaluated the inhibitory effect of afatinib and RP4010 on intracellular Ca2+ oscillations in KYSE-150, a human esophageal squamous cell carcinoma cell line, using both experimental and mathematical simulations. Our mathematical simulation of Ca2+ oscillations could fit well with experimental data responding to afatinib or RP4010, both separately or in combination. Guided by simulation, we were able to identify a proper ratio of afatinib and RP4010 for combined treatment, and such a combination presented synergistic anticancer-effect evidence by experimental measurement of intracellular Ca2+ and cell proliferation. This intracellular Ca2+ dynamic-based mathematical simulation approach could be useful for a rapid and cost-effective evaluation of combined targeting therapy drugs.

Pickle recruits retinoblastoma related 1 to control lateral root formation in arabidopsis - Ötvös, Krisztina; Miskolczi, Pál; Marhavý, Peter; Cruz-Ramírez, Alfredo; Benková, Eva; Robert, Stéphanie; Bakó, László (International Journal of Molecular Sciences)
Lateral root (LR) formation is an example of a plant post-embryonic organogenesis event. LRs are issued from non-dividing cells entering consecutive steps of formative divisions, proliferation and elongation. The chromatin remodeling protein PICKLE (PKL) negatively regulates auxin-mediated LR formation through a mechanism that is not yet known. Here we show that PKL interacts with RETINOBLASTOMA-RELATED 1 (RBR1) to repress the LATERAL ORGAN BOUNDARIES-DOMAIN 16 (LBD16) promoter activity. Since LBD16 function is required for the formative division of LR founder cells, repression mediated by the PKL–RBR1 complex negatively regulates formative division and LR formation. Inhibition of LR formation by PKL–RBR1 is counteracted by auxin, indicating that, in addition to auxin-mediated transcriptional responses, the fine-tuned process of LR formation is also controlled at the chromatin level in an auxin-signaling dependent manner.

LINC01133 inhibits invasion and promotes proliferation in an endometriosis epithelial cell line - Yotova, Iveta; Hudson, Quanah J.; Pauler, Florian; Proestling, Katharina; Haslinger, Isabella; Kuessel, Lorenz; Perricos, Alexandra; Husslein, Heinrich; Wenzl, René (International Journal of Molecular Sciences)
Endometriosis is a common gynecological disorder characterized by ectopic growth of endometrium outside the uterus and is associated with chronic pain and infertility. We investigated the role of the long intergenic noncoding RNA 01133 (LINC01133) in endometriosis, an lncRNA that has been implicated in several types of cancer. We found that LINC01133 is upregulated in ectopic endometriotic lesions. As expression appeared higher in the epithelial endometrial layer, we performed a siRNA knockdown of LINC01133 in an endometriosis epithelial cell line. Phenotypic assays indicated that LINC01133 may promote proliferation and suppress cellular migration, and affect the cytoskeleton and morphology of the cells. Gene ontology analysis of differentially expressed genes indicated that cell proliferation and migration pathways were affected in line with the observed phenotype. We validated upregulation of p21 and downregulation of Cyclin A at the protein level, which together with the quantification of the DNA content using fluorescence-activated cell sorting (FACS) analysis indicated that the observed effects on cellular proliferation may be due to changes in cell cycle. Further, we found testis-specific protein kinase 1 (TESK1) kinase upregulation corresponding with phosphorylation and inactivation of actin severing protein Cofilin, which could explain changes in the cytoskeleton and cellular migration. These results indicate that endometriosis is associated with LINC01133 upregulation, which may affect pathogenesis via the cellular proliferation and migration pathways.

Cardiolipin-containing lipid membranes attract the bacterial cell division protein diviva - Labajová, Naďa; Baranova, Natalia S.; Jurásek, Miroslav; Vácha, Robert; Loose, Martin; Barák, Imrich (International Journal of Molecular Sciences)
DivIVA is a protein initially identified as a spatial regulator of cell division in the model organism Bacillus subtilis, but its homologues are present in many other Gram-positive bacteria, including Clostridia species. Besides its role as topological regulator of the Min system during bacterial cell division, DivIVA is involved in chromosome segregation during sporulation, genetic competence, and cell wall synthesis. DivIVA localizes to regions of high membrane curvature, such as the cell poles and cell division site, where it recruits distinct binding partners. Previously, it was suggested that negative curvature sensing is the main mechanism by which DivIVA binds to these specific regions. Here, we show that Clostridioides difficile DivIVA binds preferably to membranes containing negatively charged phospholipids, especially cardiolipin. Strikingly, we observed that upon binding, DivIVA modifies the lipid distribution and induces changes to lipid bilayers containing cardiolipin. Our observations indicate that DivIVA might play a more complex and so far unknown active role during the formation of the cell division septal membrane.

Xyloglucan remodeling defines auxin-dependent differential tissue expansion in plants - Velasquez, Silvia Melina; Guo, Xiaoyuan; Gallemi, Marçal; Aryal, Bibek; Venhuizen, Peter; Barbez, Elke; Dünser, Kai Alexander; Darino, Martin; Pӗnčík, Aleš; Novák, Ondřej; Kalyna, Maria; Mouille, Gregory; et al. (International Journal of Molecular Sciences)
Size control is a fundamental question in biology, showing incremental complexity in plants, whose cells possess a rigid cell wall. The phytohormone auxin is a vital growth regulator with central importance for differential growth control. Our results indicate that auxin-reliant growth programs affect the molecular complexity of xyloglucans, the major type of cell wall hemicellulose in eudicots. Auxin-dependent induction and repression of growth coincide with reduced and enhanced molecular complexity of xyloglucans, respectively. In agreement with a proposed function in growth control, genetic interference with xyloglucan side decorations distinctly modulates auxin-dependent differential growth rates. Our work proposes that auxin-dependent growth programs have a spatially defined effect on xyloglucan’s molecular structure, which in turn affects cell wall mechanics and specifies differential, gravitropic hypocotyl growth.
Keywords: auxin; growth; cell wall; xyloglucans; hypocotyls; gravitropism

Evaluating Face2Gene as a tool to identify Cornelia de Lange syndrome by facial phenotypes - Latorre-Pellicer, Ana; Ascaso, Ángela; Trujillano, Laura; Gil-Salvador, Marta; Arnedo, Maria; Lucia-Campos, Cristina; Antoñanzas-Pérez, Rebeca; Marcos-Alcalde, Iñigo; Parenti, Ilaria; Bueno-Lozano, Gloria; Musio, Antonio; Puisac, Beatriz; et al. (International Journal of Molecular Sciences)
Characteristic or classic phenotype of Cornelia de Lange syndrome (CdLS) is associated with a recognisable facial pattern. However, the heterogeneity in causal genes and the presence of overlapping syndromes have made it increasingly difficult to diagnose only by clinical features. DeepGestalt technology, and its app Face2Gene, is having a growing impact on the diagnosis and management of genetic diseases by analysing the features of affected individuals. Here, we performed a phenotypic study on a cohort of 49 individuals harbouring causative variants in known CdLS genes in order to evaluate Face2Gene utility and sensitivity in the clinical diagnosis of CdLS. Based on the profile images of patients, a diagnosis of CdLS was within the top five predicted syndromes for 97.9% of our cases and even listed as first prediction for 83.7%. The age of patients did not seem to affect the prediction accuracy, whereas our results indicate a correlation between the clinical score and affected genes. Furthermore, each gene presents a different pattern recognition that may be used to develop new neural networks with the goal of separating different genetic subtypes in CdLS. Overall, we conclude that computer-assisted image analysis based on deep learning could support the clinical diagnosis of CdLS.

AcoMYB4, an Ananas comosus L. MYB transcription factor, functions in osmotic stress through negative regulation of ABA signaling - Chen, Huihuang; Lai, Linyi; Li, Lanxin; Liu, Liping; Jakada, Bello Hassan; Huang, Youmei; He, Qing; Chai, Mengnan; Niu, Xiaoping; Qin, Yuan (International Journal of Molecular Sciences)
Drought and salt stress are the main environmental cues affecting the survival, development, distribution, and yield of crops worldwide. MYB transcription factors play a crucial role in plants’ biological processes, but the function of pineapple MYB genes is still obscure. In this study, one of the pineapple MYB transcription factors, AcoMYB4, was isolated and characterized. The results showed that AcoMYB4 is localized in the cell nucleus, and its expression is induced by low temperature, drought, salt stress, and hormonal stimulation, especially by abscisic acid (ABA). Overexpression of AcoMYB4 in rice and Arabidopsis enhanced plant sensitivity to osmotic stress; it led to an increase in the number stomata on leaf surfaces and lower germination rate under salt and drought stress. Furthermore, in AcoMYB4 OE lines, the membrane oxidation index, free proline, and soluble sugar contents were decreased. In contrast, electrolyte leakage and malondialdehyde (MDA) content increased significantly due to membrane injury, indicating higher sensitivity to drought and salinity stresses. Besides the above, both the expression level and activities of several antioxidant enzymes were decreased, indicating lower antioxidant activity in AcoMYB4 transgenic plants. Moreover, under osmotic stress, overexpression of AcoMYB4 inhibited ABA biosynthesis through a decrease in the transcription of genes responsible for ABA synthesis (ABA1 and ABA2) and ABA signal transduction factor ABI5. These results suggest that AcoMYB4 negatively regulates osmotic stress by attenuating cellular ABA biosynthesis and signal transduction pathways.

Deep learning-assisted high-throughput analysis of freeze-fracture replica images applied to glutamate receptors and calcium channels at hippocampal synapses - Kleindienst, David; Montanaro-Punzengruber, Jacqueline-Claire; Bhandari, Pradeep; Case, Matthew J; Fukazawa, Yugo; Shigemoto, Ryuichi (International Journal of Molecular Sciences)
The molecular anatomy of synapses defines their characteristics in transmission and plasticity. Precise measurements of the number and distribution of synaptic proteins are important for our understanding of synapse heterogeneity within and between brain regions. Freeze–fracture replica immunogold electron microscopy enables us to analyze them quantitatively on a two-dimensional membrane surface. Here, we introduce Darea software, which utilizes deep learning for analysis of replica images and demonstrate its usefulness for quick measurements of the pre- and postsynaptic areas, density and distribution of gold particles at synapses in a reproducible manner. We used Darea for comparing glutamate receptor and calcium channel distributions between hippocampal CA3-CA1 spine synapses on apical and basal dendrites, which differ in signaling pathways involved in synaptic plasticity. We found that apical synapses express a higher density of α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) receptors and a stronger increase of AMPA receptors with synaptic size, while basal synapses show a larger increase in N-methyl-D-aspartate (NMDA) receptors with size. Interestingly, AMPA and NMDA receptors are segregated within postsynaptic sites and negatively correlated in density among both apical and basal synapses. In the presynaptic sites, Cav2.1 voltage-gated calcium channels show similar densities in apical and basal synapses with distributions consistent with an exclusion zone model of calcium channel-release site topography.